Analisis de los principales errores de redaccion en las secciones deportes y crónica roja de Diario El Nacional - Intriago Espinoza, Hjalmar Orlando (machala : universida tenica de machala, 2016)
The present research is aimed at daily study of the national. In the development of the same will be shown the drafting errors committed by the staff working in the sports and red chronicle sections. To establish what the errors were to be identified, the leonor zozaya article was taken as the guide, which was a great contribution for the development of this work. During a fortnight, from June 13 to June 27, the issues of the journal were collected for later analysis. The contents of each section of the aforementioned sections were tracked. The idea was always to find the factors that lead to the printing of the newspapers in which there is clearly evidence of writing problems. One of the fundamental aspects was not to hold talks or trainings that contribute to the professional knowledge of those who work for the environment, as well as the lack of a manual of styles that serves as a support in the work that communicators do daily. And the aspect that takes more importance is that you have not hired a professional style proofreader who is solely responsible for determining one by one the errors prior to printing so that it can reach the hands of the readers already corrected.La presente investigación tiene por objeto de estudio a diario el nacional. En el desarrollo del mismo se demostrarán los errores de redacción cometidos por el personal que labora en las secciones deportes y crónica roja. para establecer cuáles serían los errores a identificar se tomó como guía el artículo de leonor zozaya, el mismo que fue de gran aporte para el desarrollo del presente trabajo. durante quince días, desde el 13 hasta el 27 de junio se procedió a recopilar las emisiones del diario para su posterior análisis. Se efectuó el seguimiento correspondiente a los contenidos en cada noticia de las secciones antes mencionadas. La idea siempre fue encontrar los factores que deriven en la impresión de los diarios en los que claramente se evidencia problemas de redacción. Uno de los aspectos fundamentales encontrados fue el no realizar charlas o capacitaciones que contribuyan a los conocimientos profesionales de quienes laboran para el medio, además de la falta de un manual de estilos que sirva de apoyo en el trabajo que los comunicadores realizan a diario. Y el aspecto que toma mayor importancia es que no se ha contratado un corrector de estilos profesional que esté encargado exclusivamente a determinar uno a uno los errores previos a su impresión para que este pueda llegar a las manos de los lectores ya corregido.
The present research is aimed at daily study of the national. In the development of the same will be shown the drafting errors committed by the staff working in the sports and red chronicle sections. To establish what the errors were to be identified, the leonor zozaya article was taken as the guide, which was a great contribution for the development of this work. During a fortnight, from June 13 to June 27, the issues of the journal were collected for later analysis. The contents of each section of the aforementioned sections were tracked. The idea was always to find the factors that lead to the printing of the newspapers in which there is clearly evidence of writing problems. One of the fundamental aspects was not to hold talks or trainings that contribute to the professional knowledge of those who work for the environment, as well as the lack of a manual of styles that serves as a support in the work that communicators do daily. And the aspect that takes more importance is that you have not hired a professional style proofreader who is solely responsible for determining one by one the errors prior to printing so that it can reach the hands of the readers already corrected.
Keywords: REDACCION; DIARIO; PERIODICO; PRENSA; PUNTUACION; TIPEO; CRONICA; ROJA; DEPORTE